P01.045 Adherence to Tumor Treating Fields in patients with high-grade glioma - a single center experience. (19th September 2018) - Kessler, A; Weiland, J; Breun, M; Linsenmann, T; Ernestus, R; Hagemann, C; Löhr, M
Abstract: Background: The addition of alternating electric fields with low intensity (1–3 V/cm) and intermediate frequency (100–300 kHz), known as Tumor Treating Fields (TTFields), to adjuvant temozolomide after surgical resection and radiochemotherapy in patients with newly diagnosed glioblastoma (GBM) demonstrated a significant increase in progression free (PFS), overall (OS) and long-term survival in a phase III multi-center trial (EF-14 trial). Post-hoc analysis of this trial revealed a strong correlation of adherence to TTFields therapy with prolonged OS, underlining the importance of a high compliance rate. However, the visibility of the transducer arrays poses a potential social exposure of TTFields patients and their relatives, especially in female patients, and may impact therapy compliance. Here, we report on TTFields therapy adherence of thirty-four patients with high-grade glioma (HGG) who were treated with TTFields. Methods: Thirty-four patients diagnosed with GBM (28 patients) and astrocytoma WHO°III (6 patients), respectively, were treated with TTFields at our institution. Patients were introduced to the therapy during our neurooncologic consultation hours. We evaluated the compliance reports that were generated at the monthly technical check of the device. Results: The median age of HGG patients at therapy start was 53.5 years (range 32–67 years). 21 of the 28 GBM patients were newly diagnosed and the remainder had recurrences. These patients showed gender distribution female to male of 1:1.15, demonstrating a higher ratio of female patients compared to the typical GBM population with 1:1.7. Patients with newly diagnosed GBM were on TTFields therapy for a median of 6.5 months with median treatment compliance of 86.4%. No significant difference regarding compliance was observed between female (87.1%) and male (81.7%). Comparison between patients with newly diagnosed GBM and recurrent GBM showed no significant difference in therapy adherence with a median compliance of 80.0%. Astrocytoma WHO°III patients showed a compliance rate of 86.2%. Conclusion: The patients treated with TTFields at our institution showed a high median compliance to TTFields therapy irrespective of sex and diagnosis. In all groups, the compliance was substantially above the recommended 75% threshold. TTFields therapy was well accepted by high grade glioma patients, in particular by female GBM patients, at a high compliance rate.